Gastrointestinal bleeding risk assessment using HAS-Bled in atrial fibrillation patients who are receiving warfarin in Hospital Universiti Sains Malaysia - Idris, Sri Salwani Idris (2018)
There has been an increase usage of anticoagulant among atrial fibrillation worldwide. Warfarin remains one of the commonest anticoagulant use. Prior to starting treatment, bleeding risk need to be assess in order to minimize patients’ risk of bleeding. HASBLED is a simple and user friendly to use. Unfortunately, the utilization and usage of HAS-BLED prior to starting anticoagulant in HUSM was not known and not yet being studied. This study had been done to assess utilization of HAS-BLED and its impact on the occurrence of gastrointestinal bleeding (GIB). This retrospective study was performed among atrial fibrillation (AF) patients who attended INR or KRK outpatient clinic between January 2011 to December 2017. 88 patients were eligible for this study and their HAS-BLED were assess. Patients above 18 years old with AF who received warfarin were included in this study. Exclusion criteria include those who were taking warfarin for other causes than atrial fibrillation. We aimed to determine the rate of GIB among AF patients who are on warfarin, assess GIB risk using HAS-BLED and determine the association between GIB in AF patients with and without HAS-BLED. Among the selected 88 patients, the incidence rate of GIB is 5.7 cases per 100 patientyears. 44 (50%) had HAS-BLED assessment done prior to starting anticoagulant. The mean age of those who received warfarin was 64 years old with gender equally distributed. 83 (94.1%) patients who were started on warfarin had CHA2DS2 VASc score ≥2. GIB occurred in 11 (12.5%) out of 88 patients. Six (13.6%) patients were with HASBLED and 5 (11.4%) belong to the high risk group. The mean score for 44 patients with HAS-BLED was 1.92 (±0.936) and the mean score for 6 patients with GIB was much higher that was 2.83 (±0.98). The bleeding rate for every 100 patient-years was 0.53 and 2.63 for HAS-BLED score of 1 and 3 respectively. There was no association between GIB and HAS-BLED (p value= 0.747). There was association between GIB and duration of warfarin intake less than 30 days (p value <0.005). In conclusion, the utilisation of HAS-BLED remains low. There is no association between HAS-BLED and GIB. However, HAS-BLED is important to determine modifiable risk factors prior to starting warfarin to reduce GIB.